Relevance of hepatitis B surface antigen levels in patients with chronic hepatitis B during 5 year of tenofovir treatment. Issue 6 (26th August 2013) - Singh, A. K.; Sharma, M. K.; Hissar, S. S.; Gupta, E.; Sarin, S. K.
Summary The role of quantitative hepatitis B surface antigen (HBsAg) levels in patients receiving highly potent oral antiviral therapy is controversial, and here, we determined the HBsAg response in 121 chronic hepatitis B patients treated with tenofovir 300 mg daily. During tenofovir treatment, HBsAg decline of ≥1.0 log from baseline was seen in 16.1%, 16.3%, 18.4%, 34.6%, 36.4% and 11.8%, 15.2%, 14.8%, 28.6%, 20% at years 1, 2, 3, 4, 5 for HBeAg‐positive and HBeAg‐negative patients, respectively. Early decline in HBsAg levels at week 4 was predictive of subsequent significant HBsAg level decline. HBeAg seroconversion occurred in 29.9% of HBeAg‐positive patients. On multinomial logistic regression, HBsAg level decline from baseline at week 4 and week 12 or any time subsequently did not correlate with HBeAg seroconversion and HBV DNA level decline from baseline at week 4 and week 12 (OR = 3.704; 95% CI = 1.511–9.076; P = 0.006 and OR = 1.732; 95% CI = 1.032–2.867; P = 0.037, respectively) was significantly predictive of seroconversion. A small proportion of chronic HBV‐infected patients treated with tenofovir exhibit a significant (≥1.0 log) decline in HBsAg levels. Early decline in HBsAg levels at week 4 was predictive of subsequent and significant HBsAg level decline. The HBsAg decline did not correlate with HBeAg seroconversion in HBeAg‐positive patients. Reduction in HBV DNA levels at week 4 and 12 correlated with seroconversion.